Study for online range monitoring with the interaction vertex imaging method - Finck, Christian; Rinaldi, Ilaria (Physics in medicine and biology, 2017)
Ion beam therapy enables a highly accurate dose conformation delivery to the tumor due to the finite range of charged ions in matter (i.e. Bragg peak (BP)). Consequently, the dose profile is very sensitive to patients anatomical changes as well as minor mispositioning, and so it requires improved dose control techniques. Proton interaction vertex imaging (IVI) could offer an online range control in carbon ion therapy. In this paper, a statistical method was used to study the sensitivity of the IVI technique on experimental data obtained from the Heidelberg Ion-Beam Therapy Center. The vertices of secondary protons were reconstructed with pixelized silicon detectors. The statistical study used the ##IMG## [http://ej.iop.org/images/0031-9155/62/24/9220/pmbaa954eieqn001.gif] $χ^2$ test of the reconstructed vertex distributions for a given displacement of the BP position as a function of the impinging carbon ions. Different phantom configurations were used with or without bone equivalent tissue and air inserts. The inflection points in the fall-off region of the longitudinal vertex distribution were computed using different methods, while the relation with the BP position was established. In the present setup, the resolution of the BP position was about 4-5 mm in the homogeneous phantom under clinical conditions (10 6 incident carbon ions). Our results show that the IVI method could therefore monitor the BP position with a promising resolution in clinical conditions.